Maternal neuroticism predicts social anxiety in Cypriot youth: the mediating role of child personality and anxiety sensitivity. Issue 3 (2nd July 2016) - Panayiotou, Georgia
Abstract : This study examines the degree to which parental social anxiety and parental personality, specifically Neuroticism and Extraversion (N and E), predict social anxiety in youth and if this association is mediated by child personality including Anxiety Sensitivity (AS). N, E and AS are considered as temperamental traits and are highly predictive of anxiety disorders. Questionnaire data were collected from a community sample of 102 families in Cyprus. Cyprus presents a unique case for assessing family associations in young adults, since most college students still live with their family of origin. Questionnaires included the SPAI, ASI-16 and NEO-FFI. Results showed that parental social anxiety did not predict offspring anxiety. Maternal N was the most significant parental predictor and its association with child social anxiety was fully mediated by child N and AS. The role of the family in the development of anxiety and implications for cognitive behaviour therapy treatment are discussed.